MODULASI JUNCTION ANTAR SEL MENGGUNAKAN PEPTIDA KADHERIN UPAYA MENINGKATKAN PENGHANTARAN OBAT - Sinaga, Ernawati; Jois, Seetharama Seetharama; Avery, Mike; Makagiansar, Irwan (Makara Journal of Science, 2004)
Modulation of Intercellular Junction by Utilization of Cadherin Peptides as an Effort to Improve Drug Delivery. Rapid advances in combinatorial chemistry and molecular biology has influenced the discovery of many proteins, peptides and peptidomimetics as potential therapeutic agents. Unfortunately, the practical application of these potential drugs is often restricted by the difficulties of delivering them to target site(s) due to the presence of biological barriers. Recently, a new method to improve the drug delivery, that is by modulating the intercellular junction, has been evaluated. Modulation of intercellular junction could be achieved by modulating the proteins which play important role in establishing the intercellular junction, one of which is cadherin. In the present work we have demonstrated the ability of several cadherin peptides, i.e. Ac-LFSHAVSSNG-NH2 (HAV-10), Ac-SHAVSS-NH2 (HAV-6), Ac-QGADTPPVGV-NH2 (ADT-10), and Ac-ADTPPV-NH2 (ADT-6) to modulate the intercellular junction of MDCK (Madin Darby Canine Kidney) cells, this finding is a contribution to the establishment of a new method to improve the drug delivery by utilization of cadherin peptides by modulating the intercellular junction.